Escorpiões de Minas Gerais: O munícipio de Viçosa - Camargos Loureiro, Milgar (Revista Ceres, 2024)
This paper deals with quantitative and qualitative study of scorpionic species, at Vigosa County, Minas Gerais State, Brazil. Tityus serrulatus and Tityus trivittatus dorsomaculatus, were found, both belonging to Buthidae family. A survey was also made visiting six drugstores, the only existing Hospital and Public Health House to find out if anti-scorpionic serum was found and it was checked its lacking.